Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages precise data is published, it has been carefully estimated that this figure is made up of 412,000 hospital and 88,000 non-institutional workers as follows:— (a) Hospital Workers Number. % of Total. Description. 6,000 1.4 Full-time Doctors. 150,000 36.4 Regular Nurses (i.e. other than "war-time" Nurses). 100,000 24.3 Auxiliary Nurses (Civil Nursing Reserve, V.A.D's,etc.) 1,500 .4 Senior lay administrators (Superintendents and Stewards, etc.) 6,000 1.5 Junior lay administrative and clerical staff. 7,000 1.7 Technicians (Radiographers, Pharmacists, Masseuses, Almoners and Laboratory Staff). 4,500 1.1 Maintenance Staff (Engineers, Stokers, Carpenters, Handymen and, in mental hospitals, Farm Hands, etc.). 125,000 30.3 Male and Female Domestic Staff (Maids, Scrubbers, Porters, Kitchen and Laundry Staffs, etc.). 12,000 2.9 Medical Students (not strictly workers in usual sense of term, but a certain amount of hospital work is done by clinical students). 412,000 100.0 Well over half of hospital employees are professional workers. The majority of these (nurses) come from lower middle-class homes, and their lives are subject to a form of conventual regulation from the day they start training at the susceptible age of 18. The hospital is sub-divided into numerous special departments, each jealous of its own rights and privileges and highly resentful of anything that savours of encroachment upon its preserves. Craft prejudices are abundant. (b) Non-institutional Workers. — Reference must be made to workers in the Health Services, who, although not directly associated with a hospital or clinic, are in close contact with institutional work or with institutional workers in the services. The following are the chief classes of workers under this heading:— General Practitioners: Panel 17,000 Non-panel 5,700 22,700 Private Practitioners (specialists), Consultants (Harley Street type) 4,700 Doctors in the Services (peace-time figure) 1,700 „ „ Government employ ( „ „ ) 1,000 Retired (pre-war ; now absorbed in war effort) 3,900 Total doctors not being full-time hospital workers 34,000 33 15X/2/103/252